Novel low-temperature metal fuel cell

By combining Fe, Co, Cu, Al high-entropy nanomaterials with nitrogen-doped carbon nanotubes, HFeCoCuAl@CNTs electrocatalyst was prepared, which solved the problem of poor discharge performance of aluminum air batteries in low temperature environments, and achieved high efficiency and stability low temperature discharge performance.

CN119481093AActive Publication Date: 2025-02-18ZHENGZHOU UNIV

Patent Information

Application Number
CN202411511780.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Aluminum air batteries are difficult to start up in low temperature environments and the positive electrode reaction kinetics are slow, which limits the actual energy density of the battery. The commonly used precious metal catalysts are costly and have low utilization efficiency.

Method used

The HFeCoCuAl@CNTs electrocatalyst is prepared by combining high-entropy nanomaterials composed of four metal elements, Fe, Co, Cu and Al, and nitrogen-doped carbon nanotubes through solid phase mixing, calcining and HCl solution soaking to form a biphasic Structure to improve electrochemical properties.

Benefits of technology

The aluminum air battery was discharged stably for 250 hours in a low temperature environment of -30℃, and the ORR limit current density reached 6.41mAcm-2, significantly improving the discharge performance and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481093A_ABST
    Figure CN119481093A_ABST
Patent Text Reader

Abstract

The invention discloses a novel low-temperature metal fuel cell, which belongs to the technical field of energy materials and comprises the following steps: performing solid-phase mixing on Fe salt, Co salt, Cu salt, Al salt and a carbon source; wherein the carbon source is dicyandiamide; calcining the mixed powder in a nitrogen atmosphere to obtain a precursor material; the calcination temperature is 750 to 850 DEG C, and the calcination time is 1.5 to 2.5 hours; and soaking the obtained precursor material in an HCl solution, washing and drying to obtain the electrocatalyst. The preparation process of the electrocatalytic material is simple, the used raw materials are low in price and easy to implement, the assembled metal-air battery has excellent discharge performance, and meanwhile, the device can resist the cold environment of-30 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy materials, and more specifically, to an electrocatalyst for a low-temperature metal-air battery and a preparation method thereof, and a low-temperature metal fuel cell. Background Art

[0002] Metal-air batteries have made great progress in the field of new energy in recent years due to their unique advantages such as low environmental pollution, high discharge capacity and high energy density. Aluminum metal is abundant in the earth's crust. When used as aluminum-air fuel cells, the actual specific capacity is 2.3 times that of lithium-ion batteries, up to 500Wh kg -1 . In addition, aluminum-air batteries can be mechanically recharged by replacing new metal electrodes and electrolytes, making them "refuelable" batteries. However, aluminum-air batteries are difficult to self-start when in an environment of -10°C, and the slow kinetics of the positive electrode reaction limits the actual energy density of the battery. Therefore, the most commonly used cathode catalysts are precious metals such as Pt and Au with high catalytic efficiency. However, problems such as high cost and low utilization efficiency of precious metals limit their large-scale commercial production and application. Therefore, in order to enable aluminum-air batteries to be used in regional environments with complex temperatures, it is necessary to design a catalyst for metal-air batteries that is efficient and stable at low temperatures. Summary of the invention

[0003] The present invention aims at the above-mentioned problem that aluminum-air batteries are difficult to discharge at low temperatures, and in order to overcome the defects of the prior art, a method for preparing an electrocatalyst for low-temperature metal-air batteries is provided. The electrocatalytic material preparation process of the present invention is simple, the raw materials used are inexpensive, and it is easy to implement. The assembled metal-air battery has excellent discharge performance, and the device can withstand a cold environment of -30°C.

[0004] To achieve the above object, the technical solution of the present invention is as follows:

[0005] A method for preparing an electrocatalyst for a low-temperature metal-air battery comprises the following steps:

[0006] (1) solid-phase mixing of Fe salt, Co salt, Cu salt, Al salt and a carbon source; wherein the carbon source is dicyandiamide, and the mass ratio of the sum of the mass of the Fe salt, Co salt, Cu salt and Al salt to the mass of the carbon source is 1:4.5-5.5; calcining under a nitrogen gas atmosphere to obtain a precursor material; the calcination temperature is 750-850° C., and the time is 1.5-2.5 h;

[0007] (3) The obtained precursor material is immersed in a HCl solution, and the electrocatalyst HFeCoCuAl@CNTs is obtained after washing and drying.

[0008] In the present invention, HFeCoCuAl@CNTs is composed of a new type of high-entropy nanomaterial and nitrogen-doped carbon nanotubes, wherein the high-entropy alloy contains four metal elements, Fe, Co, Cu, and Al, and the nitrogen-doped carbon nanotubes are formed in situ; the prepared HFeCoCuAl@CNTs material has a dual-phase structure; due to its rich defect structure and a large number of active sites on the surface, it can be used in low-temperature aluminum-air batteries.

[0009] Furthermore, in step (1), the Fe salt, Co salt, Cu salt, and Al salt are specifically FeCl3, Co(NO3)2·6H2O, Cu(CH3COO)2, and Al(NO3)3, respectively. In the present invention, the acid radicals of these metal salts are easy to remove, and it is easier to obtain the desired product, so the above metal salts are preferably used.

[0010] Furthermore, in step (1), the mass ratio of FeCl3, Co(NO3)2·6H2O, Cu(CH3COO)2 and Al(NO3)3 is (0.7~1.2):(0.7~1.2):(0.7~1.2), preferably 1:1:1:1.

[0011] Furthermore, in step (1), the mass ratio of the sum of the masses of the Fe salt, the Co salt, the Cu salt and the Al salt to the mass ratio of the carbon source is 1:5.

[0012] Furthermore, in step (1), the solid phase mixing is ball milling mixing, and the ball milling time is 150 to 200 minutes. The raw materials are ball milled in a planetary ball mill in a forward and reverse rotation mode to mix them evenly and obtain a more uniform product.

[0013] Specifically, during ball milling, the machine may be rotated forward for 5 minutes, reversed for 5 minutes, and rested for 1 minute until the milling is completed.

[0014] Furthermore, in step (2), the calcination temperature is preferably 800° C. and the calcination time is 2 h. Under this temperature condition, carbon nanotubes CNTs can be grown in situ while ensuring the dispersibility of CNTs.

[0015] Furthermore, in step (3), the concentration of the HCl solution is 0.5 to 5 mol L -1 , the soaking time is 10 to 30 hours; preferably, the concentration of the HCl solution is 1 mol / L, and the soaking time is 24 hours. The best electrocatalyst material can be obtained by soaking in the hydrochloric acid solution of this concentration for this length of time. The best process conditions are to be able to synthesize HFeCoCuAl@CNTs catalyst.

[0016] A second object of the present invention is to provide an electrocatalyst for low-temperature metal-air batteries prepared by any of the above-mentioned preparation methods.

[0017] The present invention also aims to provide a low-temperature metal fuel cell, wherein the cathode of the low-temperature metal fuel cell comprises the electrocatalyst described above. That is, the electrocatalyst for low-temperature metal-air battery is applied to the metal fuel cell.

[0018] Furthermore, the obtained electrocatalyst material is dissolved in a naphthol aqueous solution under ultrasonic conditions, and then coated on a hydrophobic carbon cloth to obtain a modified carbon cloth electrode, which is used as the cathode of an aluminum air battery; the electrolyte of the low-temperature metal fuel cell is a cesium hydroxide solution, preferably, the concentration of the cesium hydroxide solution is 5 mol L -1 .

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] (1) The HFeCoCuAl@CNTs material prepared by the present invention has a special two-phase structure. The defect structure caused by the two-phase structure greatly improves the electrochemical performance in aluminum-air batteries. -2 At a current density of , the aluminum-air battery using this catalyst can discharge stably for 250 hours in a low temperature environment of -30°C.

[0021] (2) Alloy nanoparticles provide a large number of reactive sites, and the limiting current density of ORR can reach 6.41 mA cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a TEM image of the catalyst prepared in Example 1;

[0023] Figure 2 HAADF-STEM image of the catalyst prepared in Example 1;

[0024] Figure 3 Linear voltammetric scan of oxygen reduction performance of the catalyst prepared in Example 1;

[0025] Figure 4 Example 1 is a schematic diagram of a device of an aluminum-air battery prepared by assembling a catalyst;

[0026] Figure 5 The linear voltammetric scanning diagram of the aluminum-air battery obtained by assembling the catalysts prepared in Example 1 and Comparative Example 2 at room temperature;

[0027] Figure 6 Example 1 is prepared as a catalyst assembly and the constant current discharge performance of the aluminum-air battery at room temperature;

[0028] Figure 7 The constant current discharge performance of the aluminum-air battery obtained in Example 1 at low temperature;

[0029] Figure 8 X-ray diffraction (XRD) pattern of the catalyst prepared in Comparative Example 1;

[0030] Fig. 9 Comparative Example 1 is prepared as the constant current discharge performance of the aluminum-air battery assembled with the catalyst at room temperature;

[0031] Fig.10 Comparative Example 1 is prepared as the constant current discharge performance of the aluminum-air battery obtained by assembling the catalyst at low temperature;

[0032] Fig.11 TEM image of the catalyst prepared in Comparative Example 3;

[0033] Fig.12 Comparative Example 3 is prepared as the constant current discharge performance of the aluminum-air battery obtained by assembling the catalyst at low temperature;

[0034] Fig.13 TEM image of the catalyst prepared in Comparative Example 4;

[0035] Fig.14 Comparative Example 5 is a linear voltammetric scan diagram of the aluminum-air battery obtained by catalyst assembly at room temperature. DETAILED DESCRIPTION

[0036] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] In the following examples, all the raw materials used are common commercial products that can be purchased directly.

[0039] Example 1

[0040] The preparation method of the electrocatalyst HFeCoCuAl@CNTs material for aluminum-air battery described in this embodiment comprises the following steps:

[0041] The above-mentioned method for preparing the electrocatalyst HFeCoCuAl@CNTs material for aluminum-air battery comprises the following steps:

[0042] 1) Weigh 4 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0043] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0044] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 800℃ and kept for 2h to obtain nitrogen-doped graphite carbon nanotubes (FeCoCuAl@CNTs) supported by quaternary high entropy alloy.

[0045] 4) Weigh 20 mg of FeCoCuAl@CNTs and soak them in 20 mL of 1 M HCl solution for 24 hours. Wash them with deionized water and ethanol three times respectively and then vacuum dry them for 6 hours. The obtained black powder is the dual-phase HFeCoCuAl@CNTs catalyst.

[0046] The catalyst prepared in this example was subjected to the following tests:

[0047] TEM test: TEM test results are as follows Figure 1 The figure shows a transmission electron microscope image of HFeCoCuAl@CNTs, which shows that the alloy nanoparticles are coated by carbon nanotubes. The carbon nanotube structure is conducive to the transfer of ions and electrons in the electrocatalytic process.

[0048] HR-TEM test: Figure 2 is the HR-TEM test result, i.e., the high-resolution transmission electron microscopy image of HFeCoCuAl@CNTs. In the high-resolution transmission electron microscopy image, it can be observed that the interplanar spacings are and The lattice fringes correspond to the fcc structure and the bcc structure respectively.

[0049] Catalytic performance test:

[0050] The oxygen reduction and oxygen evolution performance tests were both tested using a three-electrode system, with the working electrode being a glassy carbon electrode loaded with the catalyst material prepared in Example 1, the counter electrode being a mercury / mercury oxide electrode, and the auxiliary electrode being a platinum wire. The electrolyte was a 0.1 M potassium hydroxide solution.

[0051] Specifically, a mixed slurry is prepared first, and the mixed slurry is composed of 5 mg of catalyst material, 480 μL of deionized water, 480 μL of ethanol and 40 μL of Nafion solution. In this embodiment, 5 μL of the mixed slurry is dripped on the glassy carbon electrode and dried naturally for use to obtain a working electrode.

[0052] The catalyst obtained in this example has good oxygen reduction and oxygen evolution catalytic performance. Figure 3 The linear voltammetric scan results of oxygen reduction of the catalyst material in this example tested at 1600 rpm are as follows: the starting potential is 1.1 V, the half-wave potential is 0.823 V, and the limiting current density is 6.41 mA cm -2 .

[0053] Aluminum-air battery performance test:

[0054] The aluminum air test device uses a polished aluminum plate as the anode and a carbon cloth modified with a catalyst (the 2 mg catalyst obtained in Example 1 is loaded on a 1*1 cm 2 The carbon cloth is attached to the air electrode as the cathode, and the electrolyte is 5M CsOH solution. This is the low-temperature metal fuel cell obtained in this embodiment, and the relevant electrical performance tests are performed on it.

[0055] Figure 4 This is a state diagram of the catalyst material of this embodiment being used as a cathode catalyst in a low-temperature aluminum-air battery.

[0056] Figure 5 The LSV curve of the aluminum-air battery obtained in Example 1 at room temperature is given, and the power density is 43 mW cm -2 . Figure 6 The constant current discharge performance diagram is shown. At 10mAcm -2 At a current density of , the aluminum-air battery can be discharged at room temperature for about 5 hours, after which the voltage will gradually decay. Figure 7 For its low temperature discharge performance, at 2mAcm -2 At a current density of , the aluminum-air battery using this electrocatalyst can discharge stably for more than 250 hours in a low temperature environment of -30°C.

[0057] Example 2

[0058] The method for preparing the electrocatalyst HFeCoCuAl@CNTs material for aluminum-air battery comprises the following steps:

[0059] 1) Weigh 4.2 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0060] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 200 minutes to obtain a uniformly mixed powder.

[0061] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 830℃ and kept for 2h to obtain nitrogen-doped graphite carbon nanotubes (FeCoCuAl@CNTs) supported by quaternary high entropy alloy.

[0062] 4) Weigh 20 mg of FeCoCuAl@CNTs and soak them in 20 mL of 1.5 M HCl solution for 20 hours. Wash them with deionized water and ethanol three times respectively and vacuum dry them for 6 hours. The obtained black powder is the dual-phase HFeCoCuAl@CNTs catalyst.

[0063] The catalyst obtained in this example was tested and showed to also have a structure of alloy nanoparticles coated by carbon nanotubes.

[0064] An aluminum-air battery was assembled according to the method in Example 1. The test conditions were consistent with those in Example 1. The obtained aluminum-air battery was tested to be able to stably discharge for more than 200 hours in a low temperature environment of -30°C.

[0065] Example 3

[0066] The method for preparing the electrocatalyst HFeCoCuAl@CNTs material for aluminum-air battery comprises the following steps:

[0067] 1) Weigh 3.8 g of dicyandiamide and place it in a mortar, then add 0.21 g of anhydrous ferric chloride, 0.21 g of cobalt nitrate hexahydrate, 0.19 g of aluminum nitrate and 0.19 g of anhydrous copper acetate in sequence.

[0068] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 190 minutes to obtain a uniformly mixed powder.

[0069] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 780℃ and kept for 2h to obtain nitrogen-doped graphite carbon nanotubes (FeCoCuAl@CNTs) supported by quaternary high entropy alloy.

[0070] 4) Weigh 20 mg of FeCoCuAl@CNTs and soak them in 20 mL of 2M HCl solution for 20 hours. Wash them with deionized water and ethanol three times respectively and vacuum dry them for 6 hours. The obtained black powder is the dual-phase HFeCoCuAl@CNTs catalyst.

[0071] The catalyst obtained in this example was tested and showed to also have a structure of alloy nanoparticles coated by carbon nanotubes.

[0072] An aluminum-air battery was assembled according to the method in Example 1. The test conditions were consistent with those in Example 1. The obtained aluminum-air battery was tested to be able to stably discharge for more than 200 hours in a low temperature environment of -30°C.

[0073] Comparative Example 1

[0074] A method for preparing an electrocatalyst HFeCoCuAl@CNTs material for an aluminum-air battery specifically comprises the following steps:

[0075] 1) Weigh 4 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0076] 2) After the metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, with the ball milling rotating alternately for 5 minutes in the forward direction and 5 minutes in the reverse direction with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0077] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 800℃ and kept for 2h to obtain nitrogen-doped graphite carbon nanotubes (FeCoCuAl@CNTs) supported by quaternary high entropy alloy.

[0078] Comparative Example 1 removes the acid etching. Compared with Example 1, Comparative Example 1 changes the phase structure of the alloy nanoparticles. Figure 8 The XRD results given show that the alloy is mainly composed of bcc phase. Fig. 9 The discharge performance diagram of the low-temperature aluminum-air battery of Comparative Example 1 is given. The test conditions are consistent with those in Example 1. It discharges for about 3 hours at room temperature. In comparison, the electrochemical performance is greatly attenuated. Fig.10 The aluminum-air battery obtained in Comparative Example 1 can be stably discharged for about 40 hours in a low temperature environment of -30°C, and the discharge time is greatly attenuated.

[0079] Comparative Example 2

[0080] 1) Weigh 4 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0081] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0082] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 800°C and kept for 2h to obtain the precursor material.

[0083] 4) Weigh 20 mg of the obtained precursor and soak it in 20 mL of 1M HCl solution for 12 hours, wash it with deionized water and ethanol for 3 times respectively, and then vacuum dry it for 6 hours to obtain a catalyst.

[0084] Compared with Example 1, the immersion time in step 4) was adjusted in Comparative Example 2. The test conditions were consistent with those in Example 1. The power density of the aluminum-air battery obtained by the test was 38 mW cm -2 .

[0085] Comparative Example 3

[0086] A method for preparing an electrocatalyst HFeCoCuAl@CNTs material for an aluminum-air battery specifically comprises the following steps:

[0087] 1) Weigh 4 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0088] 2) After the metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, with the ball milling rotating alternately for 5 minutes in the forward direction and 5 minutes in the reverse direction with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0089] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 700°C and kept for 2h to obtain a quaternary high entropy alloy / carbon composite material (FeCoCuAl / C).

[0090] 4) Weigh 20 mg of FeCoCuAl / C and soak it in 20 mL of 1 M HCl solution for 24 hours, wash it with deionized water and ethanol for 3 times respectively, and then vacuum dry it for 6 hours to obtain an electrocatalyst.

[0091] Comparative Example 3 was calcined at 700°C. Compared with Example 1, Comparative Example 3 changed the carbon treatment temperature. Fig.11 The TEM image of the catalyst prepared in Comparative Example 3 is given, and it can be seen that no carbon tubes are generated in the alloy material. Fig.12 The discharge performance diagram of the low-temperature aluminum-air battery of Comparative Example 3 is given. The discharge is about 2.4 hours at low temperature, and the electrochemical performance is greatly attenuated in comparison.

[0092] Comparative Example 4

[0093] 1) Weigh 4 g of urea and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of anhydrous copper acetate in sequence.

[0094] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0095] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 800°C and kept for 2h to obtain the precursor material.

[0096] 4) Weigh 20 mg of the obtained precursor and soak it in 20 mL of 1 M HCl solution for 24 hours, wash it with deionized water and ethanol for 3 times respectively, and then vacuum dry it for 6 hours to obtain a catalyst.

[0097] Comparative Example 4 is different from Example 1 in that the type of carbon source is changed. Fig.13 This is the TEM image of the electrocatalyst obtained in Comparative Example 4, and the metal particles are severely agglomerated.

[0098] Comparative Example 5

[0099] 1) Weigh 4 g of dicyandiamide and place it in a mortar, then add 0.2 g of anhydrous ferric chloride, 0.2 g of cobalt nitrate hexahydrate, 0.2 g of aluminum nitrate and 0.2 g of manganese acetate in sequence.

[0100] 2) After the above metal salts and dicyandiamide are preliminarily ground and mixed evenly, they are transferred to a planetary ball mill for ball milling, alternating forward rotation for 5 minutes and reverse rotation for 5 minutes with an interval of 1 minute. The total ball milling time is 179 minutes to obtain a uniformly mixed powder.

[0101] 3) The mixed powder was placed in a tube furnace and heated at 5°C min -1 The heating rate was increased from room temperature to 800°C and kept for 2h to obtain the precursor material.

[0102] 4) Weigh 20 mg of the obtained precursor and soak it in 20 mL of 1 M HCl solution for 24 hours, wash it with deionized water and ethanol for 3 times respectively, and then vacuum dry it for 6 hours to obtain a catalyst.

[0103] Comparative Example 5 Compared with Example 1, anhydrous copper acetate in the metal salt was replaced with manganese acetate. Fig.14 The LSV curve of the obtained aluminum-air battery at room temperature, with a power density of 39 mW cm -2 .

[0104] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an electrocatalyst for a low-temperature metal-air battery, characterized in that: The following steps are involved: (1) solid-phase mixing of Fe salt, Co salt, Cu salt, Al salt and a carbon source; wherein the carbon source is dicyandiamide, and the mass ratio of the sum of the mass of the Fe salt, Co salt, Cu salt and Al salt to the mass of the carbon source is 1:4.5-5.5; (2) calcining the mixed powder in a nitrogen atmosphere to obtain a precursor material; the calcination temperature is 750 to 850° C. and the time is 1.5 to 2.5 hours; (3) The obtained precursor material is immersed in an HCl solution, and an electrocatalyst is obtained after washing and drying.

2. The preparation method according to claim 1, characterized in that: In step (1), the Fe salt, Co salt, Cu salt and Al salt are FeCl3, Co(NO3)2·6H2O, Cu(CH3COO)2 and Al(NO3)3 respectively.

3. The preparation method according to claim 2, characterized in that: The mass ratio of FeCl3, Co(NO3)2·6H2O, Cu(CH3COO)2 and Al(NO3)3 is (0.7~1.2):(0.7~1.2):(0.7~1.2).

4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the sum of the masses of the Fe salt, the Co salt, the Cu salt and the Al salt to the mass ratio of the carbon source is 1:

5.

5. The preparation method according to claim 1, characterized in that: In step (1), the solid phase mixing is ball milling mixing, and the ball milling time is 150 to 200 minutes.

6. The preparation method according to claim 1, characterized in that: In step (2), the calcination temperature is 800° C. and the calcination time is 2 h.

7. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the HCl solution is 0.5 to 5 mol / L -1 The soaking time is 10 to 30 hours.

8. An electrocatalyst for low-temperature metal-air batteries prepared by any preparation method of claims 1-7.

9. A low-temperature metal fuel cell, characterized in that: The cathode of the low-temperature metal fuel cell comprises the electrocatalyst of claim 8.

10. The low temperature metal fuel cell according to claim 9, characterized in that: The obtained electrocatalyst material is dissolved in a naphthol aqueous solution under ultrasonic conditions, and then coated on a hydrophobic carbon cloth to obtain a modified carbon cloth electrode, which is used as the cathode of an aluminum-air battery; the electrolyte of the low-temperature metal fuel cell is a cesium hydroxide solution.

Citation Information

Patent Citations

  • Nitrogen-doped carbon nanotube / Co composite catalyst and preparation method and application thereof

    CN106669762A

  • Method for measuring content of recycled material including coffee material

    KR1020240166700A

  • Photoreduction catalyst, and method for synthesizing ammonia and method for decreasing nitrogen oxides in water using the same

    US20120228120A1

Cited By

  • Cathode material for low-temperature metal fuel cell as well as preparation method and application of cathode material

    CN122117938A